Relationship between Anxiety Rate with the Improvement of Blood Pressure in Patients of Elektif Properation are Surgery - Pablo Barreiro (GoAcademica Research & Publishing, 2020)
Preoperative nursing action is an action performed by the nurse in order to prepare the patient for surgical measures in order to ensure the safety of intraoperative patients. When faced with surgery actions that are not hypertensive patients may increase their blood pressure temporarily due to the two most common factors of pain, and anxiety. This study aims to determine the relationship of anxiety levels with increased blood pressure in elective preoperative patients. This research using cross sectional approach, accidental sampling sampling method. The sample of this study were 30 elective preoperative patients with no history of hypertension. Measurement of anxiety using Hamilton Anxiety Rating Scale and blood pressure using Spymomanometer. Chi square test results showed that there is a significant relationship between anxiety levels with an increase in blood pressure (pvalue = 0.023).